IMPROVING STUDENT ACTIVITIES AND LEARNING OUTCOMES THROUGH COOPERATIVE LEARNING TGT TYPE - Mustika, Mustika; Muhayyang, Maemuna; Munir, Munir (Universitas Negeri Makassar, 2025)
The purpose of this study was to determine the improvement of English Language Learning activities and outcomes of students in class VIII.4 SMP Negeri 3 Alla through TGT type Cooperative Learning model. This study used two cycles of action research. Each cycle consists of four stages, namely, planning, implementation, observation, and reflection. The subjects of this research were students of class VIII.4 SMP Negeri 3 Alla with a total of 29 students consisting of 14 boys and 15 girls. Based on all the discussion and analysis that has been done, it can be concluded that by applying the Teams Games Tournament (TGT) type cooperative learning model, it can be seen that students' learning outcomes in the English subject of Asking and Giving Opinions in class VIII.4 SMP Negeri 3 Alla has increased. After conducting research for two cycles the results obtained by using the Teams Games Tournament (TGT) type cooperative learning model, student learning outcomes have improved compared to before using it, namely in cycle I the average value was 69.48% with classical learning completeness of 41.37% while the average learning outcomes in cycle II were 78.44, while classical learning completeness was 82.75%.